A Spiritual Homecoming: Ireland in Contemporary Movies about Irish Americans - Schein, Alexandra (Current Objectives of Postgraduate American Studies, 2012)
The article discusses Irish-Americans’ journeys to Ireland in contemporary movies. In the movies Ireland literally enables: the journey affords couples, enlightens characters, and brings families together. Although the narratives at times self-consciously address stereotypes and clichés, Ireland’s beautiful scenery and charming people serve as a retreat from the American city and its postmodern vexations. Conflicts within contemporary US-American society are thus resolved by appropriating Irishness and ethnicity. By recurring to stereotypes about Irishness, the movies present the homeland as an alternative and corrective to the daily strife of modern life in the US. The protagonists’ identity crises are solved through contact with the Irish community or research into family history; and women find their role by embracing Irish traditionalism and finding an Irish husband. The movies thus illustrate the interdependence of discourses on gender, national identity, and ethnicity.